Safety Culture Approach For Healthcare And Nursing Institutions - Sepp Jaana (Economics and Business)
There are a few ways how to increase the rate of employees’ safety culture at an institution, one of these is a positive safety culture, which includes their proper attitudes, safety-related values, staff members’ professional competences, and their willingness to work. The key element in the offering of quality and safe services in healthcare is a positive safety quality according to definitions. The aim of the current paper is to identify potential predictors of employees’ safety behaviour and determine safety culture subcultures that support operational manager to develop proactive safety management systems (SMSs) and offer safety of patients and employees. Two independent surveys were the basis of the new proposed approach. Quantitative method approach was selected to investigate safety culture subcultures in Estonian healthcare and nursing institutions. According to the proposed approach, there are crucial subcultures (e.g., just, reporting, learning, professional competences, and psychosocial well-being), which should be developed and periodically evaluated within an organisation. This measurement should have a clear and shared understanding of patient safety goals and occupational health and safety (OHS). The general management of organisations should consider implementation of assessment as a proactive approach to use the SMSs. The sustainability and proactivity of the proposed approach lies in defining action plans for continuous improvement and employees’ involvement in patient safety and OHS management.